1978
DOI: 10.1111/j.1471-4159.1978.tb07849.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Malonic Acid in Rat Brain After Intracerebral Injection

Abstract: Abstract— Labeled malonic acid ([1‐14C] and [2‐14C]) was injected into the left cerebral hemisphere of anesthetized adult rats in order to determine the metabolic fate of this dicarboxylic acid in central nervous tissue. The animals were allowed to survive for 2, 5, 10. 15 or 30min. Blood was sampled from the torcular during the experimental period and labeled metabolites were extracted from the brain after intracardiac perfusion. There was a very rapid efflux of unreacted malonate in the cerebral venous blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

1978
1978
2004
2004

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…On the other hand, Koeppen and his co-workers studied malonate-related enzymes in the developing rat brain. They indicated that malonate may be involved in the brain development (Koeppen et al, 1974;Mitzen et al, 1976;Koeppen, et al, 1978). This review describes malonate metabolism in view of the biochemical discovery of enzymes that are related to metabolism, characterization of operons encoding malonate-metabolizing enzymes, physiological significance of mutants knocked-out key enzyme, and industrial application of the malonate metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Koeppen and his co-workers studied malonate-related enzymes in the developing rat brain. They indicated that malonate may be involved in the brain development (Koeppen et al, 1974;Mitzen et al, 1976;Koeppen, et al, 1978). This review describes malonate metabolism in view of the biochemical discovery of enzymes that are related to metabolism, characterization of operons encoding malonate-metabolizing enzymes, physiological significance of mutants knocked-out key enzyme, and industrial application of the malonate metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In leaf and root tissue of young soybean, malonate is present in high concentrations and is the predominant acid, but the metabolite does not accumulate as the dead-end product of a metabolic pathway 81,82) . Also, malonate is observed in rat brain and participates in development 47,48,60,61,71) . In both cases, it is likely that malonate is derived from malonylCoA produced by acetyl-CoA carboxylase.…”
Section: Introductionmentioning
confidence: 99%
“…Their biosynthesis has been studied in brain subfractions [23-291. 336 Although the occurrence of very long chain fatty acids has been demonstrated in the peripheral nervous system [7,22,30 -321, their origin or the conditions of their formation have not been examined so far [33].…”
Section: Introductionmentioning
confidence: 99%